Assessment of indoor bioaerosols in urban and rural classrooms / Nor Zaijanatul Zainal Ariff, Nur Syifa Mohamad Zahir, Rosmariani Roslan - Zainal Ariff, Nor Zaijanatul; Mohamad Zahir, Nur Syifa; Roslan, Rosmariani (2019)
Statistically, human spend most of their time at indoor environments in which making the exposure towards the harmful organisms more possible. However, children are more susceptible to environmental pollutants compared to adults, since they breathe more air relatively to their body weight and also have less ability to manage with the toxic chemicals due to their undeveloped respiratory system. The aim of this study was to determine and compare the indoor airborne bacteria and fungi as well as to discover the relationship between airborne bacteria and fungi concentration with physical parameters in urban and rural classrooms. A methodology based upon passive sampling (open plate technique) was used for this study. The technique was being done as petri dish was left open using settle plate method. From the results obtained for airborne bacteria, both urban and rural classrooms exceeded bacterial CFU acceptable limit set by DOSH (500 CFU/m³). This is mainly cause by children activities during sampling days. Other factors include human occupancy, inadequate ventilation, temperature and relative humidity. Moreover, there were no significance difference(p>0.05) of airborne bacteria concentration between urban and rural classrooms. On the other hand, all classrooms from both areas had fungi concentrations below than standard (1000 CFU/m³ ) as regulated by DOSH. The analysis result showing that there was significant different between the fungi concentrations in urban and rural areas (p<0.05). Higher fungi concentrations were found in urban area compared to rural area. Factors that contribute to this event include environmental condition during the sampling and dense vegetation across the school area. Apart from that, this study had proven that relative humidity was correlated with the growth of airborne bacteria and fungi. However, results showed uncorrelated for temperature and occupancy rate. Lower number of samples and constant temperature during sampling activities might affecting the results.